Pedagogy of Experience in Teacher Education for Learner and Teacher Autonomy - Flávia Vieira (Profile Issues in Teachers' Professional Development, 2020)
Language teacher education programmes can promote autonomy-oriented change when they are based on a transformative rationale regarding learner and teacher development. This involves adopting an experience-based approach whereby dominant ideas and practices are problematized and opportunities are provided for teachers to learn about, experience, and inquire into autonomy-oriented language teaching practices. A proposal based on the analysis and construction of cases in post-graduate teacher education is presented, in which teachers analyse and design autonomy-oriented action research experiences and produce narratives of inquiry. Six teacher narratives are analysed, showing that experience-based teacher education may enhance teachers’ agency to challenge mainstream practices and explore learner-centred teaching, thus developing professional autonomy in seeking to promote learner autonomy.